The New "Covid-19" Home Office Worker: Evolving Computer-Human Interactions and the Perceived Value of Workplace Technology - Kelly, Jamie (Technium Social Sciences Journal, 2020)
The context for this paper is the ongoing Covid-19 Global Pandemic and the guidance from the majority of nation-state governments for all central office based type workers to completely shift to working from home, advice which business and organisations adopted. Recent European research has established that 85% [1] of knowledge workers up to the Covid-19 Pandemic worked 80% or more of their time in a central office environment. Suddenly these office workers had to relocate their work into their homes without any opportunities for their employers to plan this move. Part of the challenge was access to the right technology. This problem was quickly resolved by the purchase of the relevant technology but not necessarily the new human-computer interaction mode. The focus of the field research was to assess the evolving human-computer of the office-based worker before the Covid-19 Pandemic. The paper has two intended outcomes. First, to provide short term insights to better understand the impact of rapid change of physical and technology-centric workspaces, due to Covid-19 on user behaviours and experience. Second to use the research to deliver better user experience design and collaboration and how technologies such Augmented Reality could enhance that experience.